Tindak Tutur Direktif dalam Stand up Comedy Ari Kriting: Indonesia - Oematan, Richard Roberto; Fallo, John; Kolnel, Arnot (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2023)
Directive speech acts in Ari Kriting's Stand up Comedy include the form and function of directive speech acts. This study aims to explain the form and function of directive speech acts. This type of research is descriptive qualitative research. The data source was obtained from Ari Kriting's Stand up Comedy video. Data collection techniques, namely techniques of observation and data recording and data analysis. The data analysis technique was carried out by listening to Ari Kriting's Stand up Comedy video in its entirety and translating his speech into written form and then marking the utterances that belong to the type of directive speech act. The research results in Ari Kriting's Stand up Comedy found several types of directive speech acts. These directive speech acts are: (a) Riquistives include: inviting. begging. (b) Quistions include: asking, interrogating. (c) Advisory includes: warning, suggesting.